2013 IEEE 24th International Symposium on Software Reliability Engineering (ISSRE) 2013
DOI: 10.1109/issre.2013.6698889
|View full text |Cite
|
Sign up to set email alerts
|

Improving search-based test suite generation with dynamic symbolic execution

Abstract: Abstract-Search-based testing can automatically generate unit test suites for object oriented code, but may struggle to generate specific values necessary to cover difficult parts of the code. Dynamic symbolic execution (DSE) efficiently generates such specific values, but may struggle with complex datatypes, in particular those that require sequences of calls for construction. The solution to these problems lies in a hybrid approach that integrates the best of both worlds, but such an integration needs to ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…We select EvoSuite because it represents the state of the art in search-based testing [21], [19]. To answer Q1-Q3, we run all tools on a collection of 32 popular real-world programs.…”
Section: A Subject Programs and Settingmentioning
confidence: 99%
“…We select EvoSuite because it represents the state of the art in search-based testing [21], [19]. To answer Q1-Q3, we run all tools on a collection of 32 popular real-world programs.…”
Section: A Subject Programs and Settingmentioning
confidence: 99%
“…As for any other symbolic execution approach, the results of SUSHI depend on the path exploration strategy. Our evaluation provides additional evidence of the differences and the complementarity between symbolic execution and search-based software testing approaches [2,22,31,35,55].…”
Section: Rq3: Sushi Wrt Complex Heap Inputsmentioning
confidence: 93%
“…Baars et al synthesise the execution conditions of sequences of branches, to improve the fitness function of SBST [2]. Malburg and Fraser, and Galeotti et al extend search-based test generation with local search operators that apply DSE during the search procedure [31,43]. Lakhotia et al use symbolic execution to compute alias information for the local search [41].…”
Section: Related Workmentioning
confidence: 99%
“…Baars et al use DSE in the fitness evaluation step for achieving branch coverage [BHH + 11], while Malburg and Fraser proposed to use small steps of DSE as mutation operator within EVOSUITE [MF11]. Galeotti et al observed that integrating DSE into a meta-heuristic algorithm affects the performances of the search at the point that higher coverage in a few corner cases may come at the price of lower coverage in the general case [GFA13]. Galeotti et al…”
Section: Hybrid Approachesmentioning
confidence: 99%